Identifikasi Karakteristik Perokok Aktif di Provinsi Sumatera Barat Tahun 2020 dengan Model Logistik Biner - Fizza Anindhita; Muhammad Hasbi (Jurnal Statistika dan Aplikasinya, 2022)
Cigarettes are one of the most popular products in society. Based on BPS data, the percentage of the population aged over 15 years who smoked in 2020 was 28,69 percent. Expenditure per capita to determine the order of the second largest after food and beverages, and greater than grains. This makes cigarettes one of the primary needs for most people. West Sumatra Province is one of the areas that promote smoking bans with various regional regulations related to smoking bans. However, this is not very fruitful, the number of smokers in West Sumatra is still higher than the national average of 30,08 percent in 2020. The dominant result obtained is that the majority of smokers in West Sumatra are male. Men are 11,5 times more likely to be active smokers than women. Smokers in West Sumatra are also dominated by residents with primary education status and below, which is 47 percent of the total smokers and has the greatest opportunity to be active compared to other educational statuses, which is 6,9 times. These results are expected to be determined to determine policies so that cigarette consumption in West Sumatra Province can be reduced.